Utilização de poda de árvores como fonte de carbono na redução de sulfato de resíduos de gesso. - Paiva, Gilka Maria da Silva (2023)
The present research was oriented towards the development of a process for the biological reduction of sulfate, present in gypsum residues, using tree pruning as a carbon source. The use of tree pruning waste as a carbon source brings many benefits to the environment and society, such as stimulating sustainability and the local economy, waste management, forest conservation, among others. Appropriate operational conditions were investigated, using a consortium of sulfate-reducing bacteria (BRS), in an anaerobic environment, with sonicated tree pruning residues as a carbon source. A 23 rotational central composite design (DCCR) was used, with the sonication time of the pruning residues, the initial sulfate concentration and the COD/[SO4=] ratio as independent variables. Percent sulfate reduction was used as the dependent variable, or response variable. The sonication of tree pruning has proven to be an excellent strategy in the pretreatment of lignocellulosic biomass (LCB). The use of the desirability function allowed the identification of a sulfate reduction efficiency of 85.9%. Two environmental liabilities were repurposed - tree pruning residues and gypsum waste, which could lead to a significant sustainable stage in the sulfur recovery process.